Highly Efficient Utilization of Precious Metals for Hydrogen Evolution Reaction with Photo‐Assisted Electro‐Deposited Urchin‐Like Te Nanostructure as a Template. Issue 9 (9th April 2019) - Bai, Ling; Li, Yujie; Zhao, Jun; Bao, Yunkai; Ji, Lifei; Dai, Jianying; Shi, Huilan; Yang, Fengchun; Zhang, Xin
Abstract: In this communication, the urchin‐like Te template is obtained by photo‐assisted electro‐deposition to replace trace platinum, gold and rhodium to obtain the Pt@Te‐PsS, Au@Te‐PsS and Rh@Te‐PsS catalysts in pursuit of their highly efficient utilization. The three‐dimensional structure of urchin‐like Te can not only accelerate the interface charge transfer, but also enhance the structural stability of the catalysts. Moreover, the electrons of Te are delocalized, to increase the electron density of interface and promote the hydrogen evolution reaction. Especially, the Pt@Te‐PsS catalyst with the Pt loading of only 1.08 wt % exhibits extremely outstanding electrocatalytic hydrogen evolution reaction activity. The finer hierarchical structure of Te template boosts the high HER performance with low precious metal loading, which highlights a new strategy for development of high‐efficiency electrocatalysts. Abstract : A mischievous child or a sea creature ? The urchin‐like Te template is fabricated by photo‐assisted electro‐deposition at the PsS substrate, which was then used for replacing trace Pt, Au and Rh to obtain the Pt@Te‐PsS, Au@Te‐PsS and Rh@Te‐PsS catalysts for HER. The obtained products showed excellent HER activity and stability, which achieves the highly efficient utilization of precious metals and provides an interesting method to lower their content in energy field.